Implementasi Pemikiran Roscoe Pound dalam Penyelesaian Konflik Litigasi dan Non Litigasi di Indonesia - Rahmawati, Dewi; Iskandar, Ghaida Nazhifah; Isnaeni, Yunika; Harahap, Chisa Belinda (Gunung Djati Conference Series, 2025)
This research examines the application of Roscoe Pound's theory in litigation and non-litigation conflict resolution in Indonesia, with a focus on the case study of the “Geprek Bensu” trademark dispute and the Benuaq tribe's customary land conflict. The background of this research is based on the complexity of legal conflict resolution in Indonesia which involves social and humanitarian aspects. The purpose of this research is to analyze the effectiveness of litigation and non-litigation approaches based on Roscoe Pound's thoughts on law as a tool of social engineering. This research uses a normative juridical method with a case study approach, analyzing two different cases, namely a trademark dispute resolved by litigation and a customary land conflict using a non-litigation approach. The results show that litigation settlements, such as in the “Geprek Bensu” case, tend to produce firm decisions but can worsen relations between parties. Meanwhile, the non-litigation approach in the Benuaq Tribe is more effective in maintaining social harmony and cultural values. In conclusion, Pound's theory on the balance of interests is still relevant in the context of conflict resolution in Indonesia, with the non-litigation approach being more suitable for cases involving socio-cultural aspects.